Medical Treatment of High Blood Pressure - Monge Casinelli, Carlos (1955)
95% of patients with hypertension have essential hypertension. Within 5% remaining cases can be found if the diagnosis of pheochromocytoma, or unilateral renal injury may result in the ultimate cure of hypertension. A variety of essential hypertension whose rapid evolution called malignant treatment is imperative. Must be separated from the group of chronic nephritis in lowering blood pressure, which not only relieves the patient, but breaks a vicious cycle that damages blood vessels. They should be treated all patients with malignant hypertension and all those having essential hypertension have a very high over 120 mmHg diastolic, or rapid disease progression. In other hypertensive psychotherapy and therapeutic sedative enough. Must take special precautions with arterioesclerósicos uremic patients or in whom an excessive reduction of blood pressure or sudden fall can result in cerebral thrombosis, uremia or increased respectively. The procedure or drug to choose, it will be good if a reasonable drop in blood pressure is achieved without much harm to the patient, or without causing excessive discomfort. A brief description of the main procedures or drugs currently in use becomes.